Molecular-genetic aspects of the endometrium state on the day of the tentative implantation window in women with recurrent miscarriage in the programs of assisted reproductive technologies - Golovatyuk, K. P.; Nosenko, O. M.; Makshayeva, E. T.; Trofimov, D. Yu.; Donnikov, A. E.; Kolin, V. V. (Journal of Education, Health and Sport, 2017)
More than 50% of pregnant women after the programs of assisted reproductive technologies (ART) face the problem of recurrent miscarriage (RMC), especially in the first trimester. Significant role in the development of RMC has infectious factor and chronic inflammation in the endometrium. The aim: to reveal the peculiarities of immune response mRNA genes of the inflammatory component expression in the period of the tentative implantation window (TIW) in women with RMC in ART programs. Material and methods. The main group consisted of 240 patients with RMC in ART programs; the control group included 100 conditionally healthy fertile women. On the ground of PCR reverse transcription, the mRNA of the IL-1β, IL-2, IL-10, Foxp3, TLR9, IL-2Rα cytokine genes was examined in endometrial samples obtained with the help of biopsy on the TIW day. Results. Analysis of the transcriptional profile of the immune response genes in the endometrium on TIW day revealed that the relative level of mRNA expression of the IL-1β, IL-2, Foxp3, TLR9, IL-2Rα genes did not differ significantly in the main and control groups. Statistically significant decrease in mRNA expression of IL-10 gene was observed in women with RPL. Conclusions. A feature of mRNA expression of the inflammatory component of the immune response in TIW period in women with RMC in ART programs is a decrease in the expression level of the IL-10 gene mRNA, which may be one of the reasons for the unfavorable outcomes of the onset pregnancy.